If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(2x + -1) = 4x Reorder the terms: (1 + 2x)(2x + -1) = 4x Reorder the terms: (1 + 2x)(-1 + 2x) = 4x Multiply (1 + 2x) * (-1 + 2x) (1(-1 + 2x) + 2x * (-1 + 2x)) = 4x ((-1 * 1 + 2x * 1) + 2x * (-1 + 2x)) = 4x ((-1 + 2x) + 2x * (-1 + 2x)) = 4x (-1 + 2x + (-1 * 2x + 2x * 2x)) = 4x (-1 + 2x + (-2x + 4x2)) = 4x Combine like terms: 2x + -2x = 0 (-1 + 0 + 4x2) = 4x (-1 + 4x2) = 4x Solving -1 + 4x2 = 4x Solving for variable 'x'. Reorder the terms: -1 + -4x + 4x2 = 4x + -4x Combine like terms: 4x + -4x = 0 -1 + -4x + 4x2 = 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. -0.25 + -1x + x2 = 0 Move the constant term to the right: Add '0.25' to each side of the equation. -0.25 + -1x + 0.25 + x2 = 0 + 0.25 Reorder the terms: -0.25 + 0.25 + -1x + x2 = 0 + 0.25 Combine like terms: -0.25 + 0.25 = 0.00 0.00 + -1x + x2 = 0 + 0.25 -1x + x2 = 0 + 0.25 Combine like terms: 0 + 0.25 = 0.25 -1x + x2 = 0.25 The x term is -1x. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = 0.25 + 0.25 Reorder the terms: 0.25 + -1x + x2 = 0.25 + 0.25 Combine like terms: 0.25 + 0.25 = 0.5 0.25 + -1x + x2 = 0.5 Factor a perfect square on the left side: (x + -0.5)(x + -0.5) = 0.5 Calculate the square root of the right side: 0.707106781 Break this problem into two subproblems by setting (x + -0.5) equal to 0.707106781 and -0.707106781.Subproblem 1
x + -0.5 = 0.707106781 Simplifying x + -0.5 = 0.707106781 Reorder the terms: -0.5 + x = 0.707106781 Solving -0.5 + x = 0.707106781 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = 0.707106781 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = 0.707106781 + 0.5 x = 0.707106781 + 0.5 Combine like terms: 0.707106781 + 0.5 = 1.207106781 x = 1.207106781 Simplifying x = 1.207106781Subproblem 2
x + -0.5 = -0.707106781 Simplifying x + -0.5 = -0.707106781 Reorder the terms: -0.5 + x = -0.707106781 Solving -0.5 + x = -0.707106781 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = -0.707106781 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = -0.707106781 + 0.5 x = -0.707106781 + 0.5 Combine like terms: -0.707106781 + 0.5 = -0.207106781 x = -0.207106781 Simplifying x = -0.207106781Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.207106781, -0.207106781}
| 4y+2=-8/3(8-12y) | | 3a+b-45=2a+4b+465.23+a+507.23b | | 15+.25x=20+0.05 | | 2x+4=9+6x | | -4(x-9)=42 | | 5x-12+7x+4= | | 64m^2+7=16 | | 2x+90=85 | | -3+4=-5-9 | | 2(x+6)=4(3x) | | 4x-8=(x-4) | | 36+N=63 | | 3a+b-45=2a+4b+465.23+a+103b | | 13-x/7=-1 | | -1/5a+7=(-11) | | (x+2x+5)-10=22 | | 5/8x24 | | a/b-45=2a+4b+465.23+a+103b | | 1/4(8x-16)=6x+2 | | ab-45=2a+4b+465.23+a+103b | | -15-(-8)+7= | | ab-45=2a+4b+465.23+a+103ab | | -1-6k=-7k-19 | | 2+25p^2=66 | | 10a+15a=75 | | 2x+6=-6x-34 | | -7s+4=-7-8s+4 | | 6-7i/6+7i | | 60=-5x+10 | | 8v+35=7(6v+5) | | (1/2x)=32 | | 2g-14=g |